2021
DOI: 10.3390/su13169341
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Carrot Pomace to Grow Mealworm Larvae (Tenebrio molitor)

Abstract: Edible insects are a sustainable food source to help feed the growing population. Mealworms (Tenebrio molitor) can survive on a variety of food wastes and alter their composition based on the feed source. Commercial carrot production produces an abundance of carotenoid-rich carrot pomace, which may be beneficial for mealworm larvae growth. This study uses an I-optimal response surface design to assess the effect of dehydrated carrot pomace concentrations (made up with wheat bran as the control) in the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The reduced sensory results of the insect products principally agree with their color values, mainly the lower lightness and redness and the higher yellowness results. Different studies support our sensory results [ 28 , 39 , 40 , 41 ]. For example, Choi et al [ 28 ] presented that frankfurters with increasing amounts of T. molitor showed reduced color, flavor, and overall acceptability results.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The reduced sensory results of the insect products principally agree with their color values, mainly the lower lightness and redness and the higher yellowness results. Different studies support our sensory results [ 28 , 39 , 40 , 41 ]. For example, Choi et al [ 28 ] presented that frankfurters with increasing amounts of T. molitor showed reduced color, flavor, and overall acceptability results.…”
Section: Resultssupporting
confidence: 87%
“…We used whole larvae, whereas many other authors used dried or otherwise heated insect larvae, which clearly has an impact on the proximate composition results of the insects [ 6 ]. Besides this, fat and protein concentration are also influenced by factors such as the species, age, or feeding of the insects [ 7 , 10 , 11 , 20 , 40 , 41 , 42 , 43 ]. Due to this, already published data on the protein and fat composition of H. illucens and T. molitor are quite variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The balancing of the protein and carbohydrate content, with incomplete nutrition, was proven in locusts ( Locusta migratoria L., Orthoptera: Acrididae) [ 5 ]. Different studies have examined the use of agricultural by-products [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], fish discards [ 13 ] and organic waste [ 14 ] as insect food and the effects on larval chemical composition. Researchers concluded that it is possible to rear mealworm larvae on food by-products.…”
Section: Introductionmentioning
confidence: 99%
“…The global production of carrot pomace was around 45 million tons in 2019. Carrot pomace (CP), which comprises a significant portion of carrot, is discarded during the industrial juice extraction process [3]. CP contains various biopolymers including cellulose (10-28%), hemicellulose (5-20%), lignin (2.5-7.7%), and pectin (2-8%).…”
Section: Introductionmentioning
confidence: 99%